A New Approach for Brain Tumor Detection Using Machine Learning - Elsadek Hussien Ibrahim; Shaaban Ebrahim Abo-Youssef; Khaled El-Bahnasy; Khaled Ahmed Mohamed Fathy (Dubai Medical Journal)
Introduction: The abnormal brain cells consist of brain tumor which leads to severe organ dysfunction and potentially death. These tumors exhibit a wide range of sizes, textures, and locations. Diagnosing brain tumors process is a time-consuming process requiring the expertise of radiologists. Brain tumors are classified as glioma, meningioma, pituitary, and no tumor. As patient numbers and data volumes rise, traditional methods have become costly and inefficient.